Aflatoxin Detoxification in Rice using Citric Acid - M Safara; F Zaini; SJ Hashemi; M Mahmoudi; AR Khosravi; F Shojai-Aliabadi (Tehran University of Medical Sciences, 2010)
Background: Aflatoxins cause health hazards to human and animals and has also economical problems. Therefore, the detoxification effect of citric acid was investigated in rice as the main food of Iranian people. Methods: Initially 275 samples of rice were examined for aflatoxins by HPLC. The aflatoxins contaminated samples were later treated by aqueous citric acid and detoxification of aflatoxins were quantified using HPLC. Results: Among the 275 samples analyzed, aflatoxin B1 and aflatoxin B2 were detected in 211(76.72% of total) samples. Aflatoxin B1 was detected in 203(73.82% of total) samples with a mean and standard deviation of 2.3±10.21ppb. Aflatoxin B2 together with aflatoxin B1 were detected in only 8(2.91% of total) samples with a mean and standard deviation of 1.38±2.7ppb of aflatoxin B2 and 2.99±1.56 of aflatoxin B1 respectively. Aflatoxin B1 level in 5 samples (1.82%) was above the maximum tolerated level of aflatoxin B1 in Iran (5ppb). However considering the Iranian maximum tolerated level for aflatoxins in rice (30ppb), only 3(1.09%) samples were above the 30ppb and also in regard to the European maximum tolerated level for aflatoxins in rice (4ppb), only 9(3.27%) samples were considered as higher than 4ppb. Conclusion: The HPLC assay showed that although aflatoxins with a concentration of <30 and <4 ppb in the rice samples were completely degraded, but 97.22% degradation occurred in rice contaminated with ³30 and ³4ppb when treated with 1N citric acid. These results revealed the efficacy of 1N citric acid in reducing aflatoxins levels in rice.